Ultrasonic Pulse Velocity Test Using BS Method And T-Method to Estimate Crack Depth of Concrete - Evin Yudhi Setyono (Logic : Jurnal Rancang Bangun dan Teknologi, 2023)
Ultrasonic Pulse Velocity (UPV) as a non-destructive test is commonly used on concrete crack estimation. There are several methods are applied based on the transducer configuration. Among the methods, BS (British Standard) method and T method was used in this study. On this method, transmitter was fixed at certain distance from crack and receiver was moved at several constant intervals, then crack depth was analyze from the relation between the transducer distance and the transit time curve. This research is conducted to study the accuracy of BS method and T-method in estimating the crack depth of concrete using NDT James Instrument V-Meter M-K IV. Concrete beams were made with artificial crack depth 2 cm, and 4 cm. Transducers 54kHz of UPV Mark IV were set at constant interval. Thus, the comparation of actual depth and experimentally result was analyzed. The study concluded that, the accuracy of the BS method has a better estimation result with a relative error of 27,75% and 35,95%, compare to the T-method that has 79,30% and 79,82% error.